Nghiên cứu ảnh hưởng của các loại phụ gia đến tính chất của sơn lót epoxy bảo vệ kết cấu thép trong giao thông vận tải - Thuỷ, Nguyễn Thị Bích (Vietnam Journal of Chemistry, 2012)
This paper presents the result of research on the influence of resins, the additives and plasticizers on the properties of epoxy primers. The result showed that the additive plasticizer named 02 has a good score for the long-term plasticity. The best coating was achieved with the presence of 5% active plasticizer name 02 and 0.5% silicafume rheology additive.